Understanding and Identifying Cognitive Load in Networked Learning - Kehrwald, Benjamin A.; Bentley, Brendan P. (Proceedings of the International Conference on Networked Learning, 2018)
This paper considers cognitive load theory (CLT) in the context of networked learning (NL). It aligns with NL practitioners’ efforts to understand and eliminate barriers to learning in NL situations. The ideas presented are based on the premise that by recognising and either minimising or eliminating instances of unnecessary cognitive load in NL situations educators can improve learners’ abilities to acquire and develop schema and, in doing so, educators can support learning in NL situations. The presentation brings together current thinking in cognitive load theory and descriptions of key aspects of NL to identify and describe of potential instances of cognitive load experienced by networked learners. The paper is structured in three main sections: The first section provides the background to our exploration of CLT in the context of NL. It includes an overview of CLT and its development; an overview of NL; and a definition of the problem this paper seeks to address, namely, that NL situations include a number of instances of cognitive load which may not be present in other (e.g., face-to-face; on-campus) learning situations. The second section explores common features of NL and identifies potential sources of cognitive load in NL situations. It is organised according to key features of the ’architecture’ of NL: the learning environment; learning tasks and learner activity. By identifying potential instances of cognitive load, the presentation provides a basis for, firstly, understanding cognitive load in NL; and, secondly, addressing it. Key sources of cognitive load referenced in this paper include the presentation of information in NL situations; the use of mediating technologies; the demands of managing information in connected environments; the load associated with technology-mediated social activity, including computer-mediated communication; the presentation of learning tasks; and the demands of ’learning to learn’ in NL situations. The third section of the paper identifies a potential research agenda to guide further explorations of CLT in NL including: research into technical aspects of NL to improve the presentation of information and computer interfaces; research into the use of instructional design techniques sympathetic to CLT and specifically targeting NL and engagement tasks; research to understand learning to learn online in NL from a CLT perspective.